Smart building assessments: optimizing SRI calculation using a BIM-based data exchange framework - Calandri, Maurizio; Tafelmaier, Louis; Rathje, Torben; Müller, Michael; Henzler, Tobias; Stergiaropoulos, Konstantinos; Kramp, Michael; Glatz, Andreas (Frontiers in Built Environment, 2025)
Insufficient data availability, limited calculation tools and subjective decisions by experts lead to ambiguous results when determining the Smart Readiness Indicator of a building. Moreover, it is not an integral part of the planning process. Therefore, this study presents a consistent and process-oriented planning and calculation approach. The methodology consists of the combination and exchange of information between building information modeling, labeling system, and data exchange format. It provides a consistent, seamless flow of information throughout integrated planning. This enables an automatic calculation of the planned Smart Readiness Indicator based on a floor-related functionality assessment, as proved using a mock-up. In addition, it provides a clear categorization of the necessary information for the planned components, which can be used for the verification process. Overall, this leads to a significant reduction in the time and effort required for smart building assessments while also increasing their consistency of evaluation.